MOLECULAR STATICS SIMULATION OF NANOINDENTATION USING ADAPTIVE QUASICONTINUUM METHOD - Karel Mikeš; Ondřej Rokoš; Ron H. J. Peerlings (Acta Polytechnica CTU Proceedings)
In this work, molecular statics is used to model a nanoindentation test on a two-dimensional hexagonal lattice. To this end, the QuasiContinuum (QC) method with adaptive propagation of the fully resolved domain is used to reduce the computational cost required by the full atomistic model. Three different adaptive mesh refinement criteria are introduced and tested, based on: (i) the Zienkiewicz–Zhu criterion (used for the deformation gradient), (ii) local atoms’ site energy, and (iii) local lattice disregistry. Accuracy and efficiency of individual refinement schemes are compared against the full atomistic model and obtained results are discussed.